2021
DOI: 10.1186/s12890-021-01642-z
|View full text |Cite
|
Sign up to set email alerts
|

Clinical characteristics of patients with chronic cough in Guangdong, China: a multicenter descriptive study

Abstract: Background The clinical characteristics of patients with chronic cough are reported only in single-center survey in China, being significantly different from that in western countries. Here, we performed a multicenter study to describe the clinical characteristics of chronic cough patients. Methods A cross-sectional observational survey was conducted in thirteen tertiary hospitals of Guangdong, South China. Relevant data were recorded using a stan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 37 publications
1
4
0
Order By: Relevance
“…A significant positive correlation between age and the number of nocturnal coughs emerged here ( Fig 12A ), as was also found in [ 40 ]. Finally, the comparison of the cough rate in terms of gender revealed that women coughed significantly more than men during the night, as was also found in [ 40 ] on a database of 100 subjects (65 women), and in [ 41 ] on a database of 933 subjects (52.2% women). One possible explanation for this outcome is that women have more episodes of upper airway resistance, which may cause cough episodes [ 42 ].…”
Section: Discussionsupporting
confidence: 72%
“…A significant positive correlation between age and the number of nocturnal coughs emerged here ( Fig 12A ), as was also found in [ 40 ]. Finally, the comparison of the cough rate in terms of gender revealed that women coughed significantly more than men during the night, as was also found in [ 40 ] on a database of 100 subjects (65 women), and in [ 41 ] on a database of 933 subjects (52.2% women). One possible explanation for this outcome is that women have more episodes of upper airway resistance, which may cause cough episodes [ 42 ].…”
Section: Discussionsupporting
confidence: 72%
“…During the last decades, several international and national guidelines have been developed for guiding the management of CC patients [7][8][9]. Several studies reported the characteristics of CC among patients visiting clinics [10][11][12][13][14]; however, there is limited knowledge about cough characteristics and healthcare journey in the community. Large general population-based studies [15][16][17] reported the prevalence of CC and its impact on health-related QoL; they mostly reported the simple presence of CC but lacked detailed cough information because they were designed to investigate general health issues.…”
Section: Introductionmentioning
confidence: 99%
“…Consecutive and unselected patients attending clinics for chronic cough were invited to participate in this survey from August 2017 to August 2018. Details of the study protocol have been described previously (23). Briefly, patients were enrolled if they had an isolated chronic cough (>8 weeks), no overt lung abnormalities, and an age of 15 years or more.…”
Section: Study Design and Participantsmentioning
confidence: 99%
“…A total of 1,384 patients with cough were screened, and 933 (67.4%) met the criteria and were included in this study. The patient numbers and reasons for exclusion have been previously reported (23). The median age of the patients was 40.0 (IQR, 31.0-52.0) years, with 52.2% of them being female (Table 1).…”
Section: Demographicsmentioning
confidence: 99%